Feasibility and potential diagnostic value of [18F]PI-2620 PET in patients with down syndrome and Alzheimer’s disease: a case series - Olivia Wagemann; Olivia Wagemann; Matthias Brendel; Nicolai Franzmeier; Nicolai Franzmeier; Nicolai Franzmeier; Georg Nübling; Georg Nübling; Johannes Gnörich; Mirlind Zaganjori; Catharina Prix; Anna Stockbauer; et al. (Frontiers in Neuroscience)
Purpose of the reportAdults with Down Syndrome (DS) have a substantially increased risk for Alzheimer’s disease (AD) due to the triplicated amyloid-precursor-protein gene on chromosome 21, resulting in amyloid and tau accumulation. However, tau PET assessments are not sufficiently implemented in DS-AD research or clinical work-up, and second-generation tau tracers such as [18F]PI-2620 have not been thoroughly characterized in adults with DS. We aim at illustrating feasibility and potential diagnostic value of tau PET imaging with [18F]PI-2620 for the diagnosis of DS-AD.Materials and methodsFive adults with DS (40% female, aged 43–62) and cognitive decline underwent clinical assessments, neuropsychological testing, lumbar puncture and multimodal neuroimaging. All underwent [18F]PI-2620 tau PET. Visual read of tau PET scans was performed by three blinded raters, assessing increased tracer uptake in brain areas corresponding to the six Braak stage regions and basal ganglia.ResultsVisual read of tau burden revealed three tau-positive individuals which corresponded to their clinical decline while two cognitively stable individuals were rated as negative. Rating showed high inter-rater reliability for all Braak stages.ConclusionTau PET imaging is a feasible and important biomarker assessment in the differential diagnosis of cognitive decline in adults with DS at risk of developing AD.